Safety Awareness: Efforts to Increase the Work Productivity of Indonesian Migrant Workers - Evi Widowati; Ratna Dewi Kusumaningtyas; Ummi Nur Laila Sulistyani; Fitra Aulia Rahma; Aza Putri Anisa; Ayu Fadilah Wahid (Universitas Negeri Semarang, 2025)
Unbalanced population growth caused by high birth rates, low mortality, and uneven population distribution poses various challenges. One of the impacts is the increasing number of workers who choose to work abroad. In 2024, there will be 297,434 Indonesian Citizens working as Indonesian Migrant Workers (PMI), with the most placements in Hong Kong (99,773), Taiwan (84,581), and Malaysia (51,732). PMI contributes significantly to the national economy through foreign exchange reserves. However, some of them also face various unfair treatment, such as low wages, violence, confiscation of documents, excessive working hours, and an inadequate work environment, in addition to many complaints related to illness, work accidents, and death. The literature review results related to PMI in Hong Kong show that PMIs still face problems related to Occupational Safety and Health (OSH). With a lack of awareness about OSH rights, this condition will worsen. Therefore, there is a need for intervention in safety awareness training to increase workers' understanding and awareness of OSH. This training aims to improve workers' knowledge to reduce the number of work accidents and increase productivity. The results of the qualitative analysis showed that training increased participants' knowledge; therefore, PMI needed to conduct refresher training regularly to improve their safety awareness.